A kind of electrolyte for negative electrode-free solid-state battery and preparation method thereof

By pre-installing the current collector in a negative electrode-free solid-state battery and forming a close bond with the electrolyte layer, the problems of large interface impedance and low lithium ion retractability are solved, and more stable lithium deposition and higher battery cycle stability are achieved.

CN118970198BActive Publication Date: 2025-04-08BOYAN JIAXIN (BEIJING) TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411280771.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-04-08
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

There are problems in negative electrode-free solid-state batteries with large interface impedance, irregular lithium deposition and low lithium ion retractability, resulting in poor battery performance.

Method used

By immersing the foam copper sheet into an impregnation liquid containing lithium-philic metal and lithium-enhancing salt, a substrate with pre-installed current collector was obtained, and the electrolyte pre-coating liquid was then poured onto the substrate, dried and microwaved to form a tightly bound solid electrolyte to form a Li-Sn alloy to guide lithium deposition.

Benefits of technology

The compatibility between the contact interface between the current collector layer and the electrolyte layer is improved, the interface impedance is reduced, the reintercalation rate of lithium ions is improved, the growth of lithium dendrites is stabilized, the service life of the current collector is extended, and the cycle stability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970198B_ABST
    Figure CN118970198B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of anode-free solid-state batteries, and specifically to an electrolyte for anode-free solid-state batteries and a preparation method thereof. The preparation method comprises the following steps: immersing a foam copper sheet in an impregnation solution containing a lithium-philic metal and a lithium-supplementing salt to obtain a substrate; pouring an electrolyte pre-coating solution on the substrate, and after drying and microwave curing, obtaining a solid electrolyte with a pre-set current collector. The preparation method first obtains a pre-set current collector loaded with rich lithium-philic sites, and then pours the electrolyte pre-coating solution on the substrate. After drying and microwave curing, the current collector layer can form a close combination with the electrolyte layer in an upper and lower alternating "gear-shaped" manner under the action of microwaves, which can promote the ion and electron conductivity on the solid electrolyte / negative electrode current collector side and guide the deposition of lithium on the current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anode-free solid-state batteries, and in particular to an electrolyte for anode-free solid-state batteries and a preparation method thereof. Background Art

[0002] In recent years, the rapid development of electronic technology and electric vehicles has put forward higher requirements for the energy density and cycle stability of lithium-ion batteries. All-solid-state metal lithium batteries have higher energy density and safety. Compared with traditional liquid lithium batteries, all-solid-state metal lithium batteries have more obvious comparative advantages. All-solid-state metal lithium batteries usually use metal lithium negative electrodes. The cost of metal lithium negative electrodes is high, the preparation process is complicated, and the compatibility of lithium metal and solid electrolytes is poor. In order to overcome the above problems, technicians have designed all-solid-state batteries without negative electrodes. Taking the active material on the negative electrode side is lighter, which is conducive to further improving the energy density of all-solid-state batteries; however, all-solid-state batteries without negative electrodes have problems such as large interface impedance, irregular lithium deposition and low lithium ion reinsertion rate. At this time, the design of the contact surface between the solid electrolyte body and the current collector side in the all-solid-state battery without negative electrodes is particularly important.

[0003] The Chinese invention patent with publication number CN113285117A discloses a composite solid electrolyte, which includes an oxide solid electrolyte, a sintering aid and a lithium halide, which can eliminate impurities on the surface of the oxide solid electrolyte and convert it into lithium halide in situ. The formation of lithium halide can block the continued reaction between the oxide solid electrolyte and water and carbon dioxide in the air, thereby improving the stability of the oxide solid electrolyte in the air; the sintering aid can fill the gaps between the oxide solid electrolyte grains, improve the density of the oxide solid electrolyte, reduce the grain boundary resistance of the oxide solid electrolyte, and further improve the performance of the composite solid electrolyte. Although the electrolyte solves the air stability problem outside the battery system of the solid electrolyte and the grain boundary resistance in the battery system, it has no positive effect on problems such as lithium deposition at the interface.

[0004] The Chinese invention patent with publication number CN115911524A discloses an electrolyte sheet with metal oxide modified SSE surface, which uses metal oxides of a non-negative solid-state lithium battery to modify the SSE (solid electrolyte) surface to form an electrolyte sheet, solving the compatibility problem between the SSE and the current collector interface. However, the tightness of the solid electrolyte and its current collector still needs to be improved, and the lithium ions of the positive electrode need to be consumed to modify the interface.

[0005] In summary, the current negative electrode-free lithium-ion batteries still cannot simultaneously solve the dual problems of poor compatibility of the current collector interface and lithium deposition at the interface. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an electrolyte for a negative electrode-free solid-state battery and a preparation method thereof, which can improve the compatibility of a current collector interface and lithium deposition at the interface.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing an electrolyte for a negative electrode-free solid-state battery, comprising the following steps: immersing a foam copper sheet in an impregnation solution containing a lithium-philic metal and a lithium-supplementing salt to obtain a substrate; pouring an electrolyte pre-coating liquid on the substrate, and after drying and microwave curing, obtaining a solid electrolyte with a pre-set current collector.

[0008] Another technical solution adopted by the present invention is: an electrolyte for a negative electrode-free solid-state battery is prepared by the above-mentioned preparation method.

[0009] The beneficial effect of the present invention is that the present invention provides a method for preparing a solid electrolyte including a pre-set current collector ("negative electrode" side). The pre-set current collector with rich lithium-affinity sites is obtained by immersing the foam copper sheet in an impregnation solution containing a lithium-affinity metal and a lithium-supplementing salt; the electrolyte pre-coating solution is then poured on the substrate, and after drying and microwave curing, the current collector layer can form a close combination of an upper and lower alternating "gear shape" with the electrolyte layer under the action of microwaves, which can promote the ion and electron conductivity on the solid electrolyte / negative electrode current collector side; at the same time, a Li-Sn alloy is generated at the interface between the electrolyte and the current collector, guiding the deposition of lithium on the current collector, thereby inhibiting lithium dendrites, and further stabilizing the battery structure in a negative electrode-free all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a comparison chart of the impedance test results of the solid electrolyte with a pre-set current collector in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0011] Figure 2 It is a comparison chart of the cycle performance test results of the solid electrolyte with pre-set current collector of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0012] Figure 3 It is a schematic structural diagram of a solid electrolyte with a pre-set current collector according to Example 4 of the present invention;

[0013] Description of labels:

[0014] 1. Polymer electrolyte layer; 2. Foam copper current collector layer; 3. Tin metal particles. DETAILED DESCRIPTION

[0015] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0016] A method for preparing an electrolyte for a negative electrode-free solid-state battery comprises the following steps: immersing a foam copper sheet in an impregnation solution containing a lithium-philic metal and a lithium-supplementing salt to obtain a substrate; pouring an electrolyte pre-coating solution on the substrate, and obtaining a solid electrolyte with a pre-set current collector after drying and microwave curing.

[0017] From the above description, it can be seen that the beneficial effect of the present invention is that: the present invention obtains a pre-set current collector loaded with rich lithium-philic sites by immersing the foam copper sheet into an impregnation solution containing a lithium-philic metal and a lithium-supplementing salt. The lithium-philic sites can effectively protect the current collector, thereby extending the service life of the current collector.

[0018] The electrolyte pre-coating liquid is then poured on the substrate, dried and microwave cured. Under the microwave strengthening effect, the foam copper current collector with micropores on the surface has a large micropore curvature. During the polymerization process, the temperature of the current collector rises rapidly, and it can form a close combination of "gear-shaped" alternations with the electrolyte layer, which promotes the ion and electron conductivity on the solid electrolyte / negative electrode current collector side; at the same time, it improves the compatibility of the contact interface between the current collector layer and the electrolyte layer, reduces the interface impedance, and increases the reinsertion rate of lithium ions. Li-Sn alloy is generated at the interface between the electrolyte and the current collector, which guides the deposition of lithium on the current collector, thereby inhibiting the growth of lithium dendrites, reducing the amount of dead lithium, further stabilizing the battery structure of the negative electrode-free all-solid-state battery, extending the service life of the current collector, and improving the cycle stability of the battery. The present invention pre-places the negative electrode side current collector on the electrolyte, which reduces the assembly steps and improves the engineering efficiency when assembling the negative electrode-free all-solid-state battery.

[0019] Furthermore, the preparation method of the impregnation solution is specifically as follows: adding stannous chloride, lithium supplement salt, lithium-philic metal and dispersant into anhydrous ethanol, and performing ultrasonic dispersion to form the impregnation solution.

[0020] Furthermore, the lithium supplement salt is an inorganic lithium salt.

[0021] Furthermore, the inorganic lithium salt is LiClO 4 (lithium perchlorate), lithium tetrafluoroborate (LiBF 4 ) lithium hexafluoroarsenate (LiAsF 6 ) and lithium hexafluorophosphate (LiPF 6 ), at least one of lithium chloride, lithium sulfate, lithium nitrate, lithium carbonate and lithium hydroxide.

[0022] Furthermore, the lithium-philic metal is tin powder.

[0023] From the above description, it can be seen that the activity of the tin metal embedded in the surface of the current collector is greater than that of copper. Tin loses electrons before copper. In a corrosive / oxidative environment, tin metal can effectively protect the copper current collector and extend the service life of the current collector.

[0024] Furthermore, the amount of dispersant added is 1-20 ml.

[0025] Preferably, the amount of dispersant added is 3-8 ml.

[0026] Furthermore, the dispersant is OP-10 or NMP (N-methylpyrrolidone).

[0027] Furthermore, the impregnation solution includes, by weight, 2 to 5 parts of stannous chloride, 1.5 to 30 parts of lithium supplementing salt and 0.1 to 20 parts of lithium-philic metal.

[0028] Preferably, the impregnation solution includes 2 to 5 parts of stannous chloride, 1.5 to 5 parts of lithium supplementing salt and 0.1 to 6 parts of lithium-philic metal in parts by weight.

[0029] Furthermore, the ultrasonic dispersion time is 5 to 20 minutes.

[0030] Furthermore, the immersion time is 20 to 30 seconds.

[0031] From the above description, it can be seen that the purpose of ultrasonic dispersion is to obtain a uniform impregnation solution. If the time is too long, it will affect the preparation efficiency. The impregnation time should not be too long, otherwise it will cause the temperature to be too high and bubbles to form, affecting the impregnation effect. In addition, the suspended particles inside the impregnation solution will settle. Continuously increasing the impregnation time will not make the impregnation effect better, but will affect the uniformity of the embedded material in the matrix.

[0032] Furthermore, the preparation method of the electrolyte pre-coating liquid is: dissolving PEO (polyethylene oxide), PAN (polyacrylonitrile) and an organic lithium salt in a mixed solvent of DMF (N,N-dimethylformamide) and acetonitrile and stirring to obtain the electrolyte pre-coating liquid.

[0033] From the above description, it can be seen that the pre-coating liquid is mainly composed of an organic solvent. In order to form a uniform organic liquid phase, the lithium salt needs to be an organic lithium salt.

[0034] Further, the organic lithium salt is at least one of LTFSI (lithium bis(trifluoromethylsulfonyl)imide), lithium borate oxalate (LiBOB) and lithium difluorooxalate borate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tert-butoxide and 5-sulfo-1,3-phthalic acid monolithium salt.

[0035] Furthermore, the mass ratio of PEO, PAN and organic lithium salt is 10-19:1-10:1-5.

[0036] Preferably, the mass ratio of PEO, PAN and organic lithium salt is 15-19:1-3:1-3.

[0037] From the above description, it can be seen that PAN and PEO are mixed in the electrolyte pre-coating solution, and PAN acts as a cross-linking agent, and the resulting structure has high mechanical strength and ionic conductivity. The PAN content should not be too much, otherwise it will increase the crystallinity of the copolymer and reduce the ionic conductivity.

[0038] Furthermore, the total mass of PEO, PAN and the organic lithium salt is 15-65% of the mass of the electrolyte pre-coating liquid.

[0039] Preferably, the total mass of PEO, PAN and the organic lithium salt is 15-35% of the mass of the electrolyte pre-coating liquid.

[0040] From the above description, it can be seen that the greater the mass fraction of PEO, PAN and organic lithium salt (solute), the shorter the initial drying time after casting the film layer and the greater the film thickness under the same mold.

[0041] Furthermore, the mass of the mixed solvent is 35-85% of the mass of the electrolyte pre-coating liquid.

[0042] Preferably, the mass of the mixed solvent is 60-85% of the mass of the electrolyte pre-coating liquid.

[0043] Furthermore, the mass ratio of DMF to acetonitrile in the mixed solvent is 1:1-5.

[0044] Furthermore, the drying condition is: drying at 50° C. for 10 to 12 hours.

[0045] From the above description, it can be seen that if the drying temperature is too high, the uniformity of the film will be affected. If the drying time is too long, the solvent evaporation efficiency will be reduced.

[0046] Furthermore, the film thickness formed by the electrolyte pre-coating liquid after drying is 20 to 260 um.

[0047] Preferably, the film thickness formed by the electrolyte pre-coating liquid after drying is 50-100 um.

[0048] From the above description, it can be seen that if the film thickness is less than 20um, when the substrate temperature reaches 150℃, it will cause the film to reflow, causing part of the substrate to be exposed, thereby endangering the safety performance of the battery. If the film thickness is greater than 150um, after the film and other components form a battery, it will not only cause the lithium ion transmission distance to become longer, but also reduce the volume energy density of the battery.

[0049] Furthermore, microwave curing is specifically as follows: placing the dried material under a microwave field, setting the microwave power to 200-400W, heating the microwave temperature to 100-150°C, then cooling by 10-50°C, repeating the heating and cooling steps at least twice, and cooling to room temperature after the last heating.

[0050] Further, preferably, the heating and cooling steps are repeated 2 to 10 times.

[0051] From the above description, it can be seen that during microwave curing, multiple heating is performed to ensure that the polymer is fully in contact with the gaps in the substrate, and the temperature needs to be lowered to room temperature after the last heating to allow the polymer to be more tightly bonded to the substrate.

[0052] Another technical solution adopted by the present invention is: an electrolyte for a negative electrode-free solid-state battery is prepared by the above-mentioned preparation method.

[0053] Another technical solution adopted by the present invention is: using the above-mentioned electrolyte for anode-free solid-state battery to prepare anode-free solid-state battery, comprising the following steps:

[0054] Step 1: Coat the positive electrode slurry on an aluminum foil with a thickness of 5 to 15 μm to a thickness of 50 to 200 μm, and then dry at 80 to 200 ° C to obtain an electrode sheet; roll the electrode sheet to control the compaction density of the active material to 0.8 to 3.7 mg / cm 3 , and then cut to obtain the positive electrode sheet;

[0055] Step 2: stack the positive electrode sheet and the solid electrolyte containing the pre-set current collector and heat them to 50-150°C, and press them at a pressure of 0.01-10Mp to obtain a negative electrode-free all-solid-state battery.

[0056] Embodiment 1 of the present invention is: a method for preparing an electrolyte for a negative electrode-free solid-state battery, comprising the following steps:

[0057] S1. Prepare the impregnation solution: first prepare 100 ml of 20 g / L stannous chloride-ethanol solution, add 1.5 g LiClO 4 , 0.1g tin powder, and at the same time, 2mL OP-10 was dropped and ultrasonically dispersed for 20min to form an impregnation solution.

[0058] Preparation of electrolyte pre-coating solution: 1.8 g PEO, 0.2 g PAN and 0.15 g LTFSI were dissolved in 30 mL of mixed solvent and magnetically stirred for 20 h to obtain electrolyte pre-coating solution; the mixed solvent was composed of DMF and acetonitrile in a mass ratio of 1:2.

[0059] S2, immersing the foam copper sheet in the impregnation solution for 25 seconds, and drying it in a vacuum oven to obtain a substrate;

[0060] S3. Place the substrate on a glass table, use a casting method to cast the electrolyte pre-coating liquid on the substrate, dry it at 50°C for 11 hours, and form an electrolyte film with a thickness of 100um on the substrate; then place it under a microwave field, set the microwave power to 300W, use microwave heating to heat the preset current collector temperature to 120°C, then cool it down by 20°C, repeat the heating and cooling steps twice, and cool it to room temperature after the last heating; then dry the remaining solvent to obtain a solid electrolyte with a preset current collector.

[0061] Embodiment 2 of the present invention is: a method for preparing an electrolyte for a negative electrode-free solid-state battery, comprising the following steps:

[0062] S1. Prepare the impregnation solution: first prepare 100 ml of 50 g / L stannous chloride-ethanol solution, add 30 g LiBF 4 , 20g tin powder, and at the same time drop 20mL OP-10, and ultrasonically disperse for 18min to form an impregnation solution.

[0063] Preparation of electrolyte pre-coating solution: 1.9 g PEO, 1 g PAN and 0.55 g LiBOB were dissolved in 50 mL of mixed solvent and magnetically stirred for 24 h to obtain electrolyte pre-coating solution; the mixed solvent consisted of DMF and acetonitrile in a mass ratio of 1:5.

[0064] S2, immersing the foam copper sheet in the impregnation solution for 20 seconds, and drying it in a vacuum oven to obtain a substrate;

[0065] S3. Place the substrate on a glass table, use a casting method to cast the electrolyte pre-coating liquid on the substrate, dry it at 50°C for 12 hours, and form an electrolyte film with a thickness of 260um on the substrate; then place it under a microwave field, set the microwave power to 400W, use microwave heating to heat the preset current collector temperature to 100°C, then cool it down by 10°C, repeat the heating and cooling steps twice, and cool it to room temperature after the last heating; then dry the remaining solvent to obtain a solid electrolyte with a preset current collector.

[0066] Embodiment 3 of the present invention is: a method for preparing an electrolyte for a negative electrode-free solid-state battery, comprising the following steps:

[0067] S1. Prepare the impregnation solution: first prepare 100 ml of 30 g / L stannous chloride-ethanol solution, add 5 g LiAsF 6 , 3g tin powder, and at the same time, 1mL NMP was dropped in and ultrasonically dispersed for 5min to form an impregnation solution.

[0068] Preparation of electrolyte pre-coating solution: 1 g PEO, 0.1 g PAN and 0.1 g LiDFOB were dissolved in 20 mL of mixed solvent and magnetically stirred for 18 h to obtain electrolyte pre-coating solution; the mixed solvent was composed of DMF and acetonitrile in a mass ratio of 1:1.

[0069] S2, immersing the foam copper sheet in the impregnation solution for 30 seconds, and drying it in a vacuum oven to obtain a substrate;

[0070] S3. Place the substrate on a glass table, use a casting method to cast the electrolyte pre-coating liquid on the substrate, dry it at 50°C for 10 hours, and form an electrolyte film with a thickness of 20um on the substrate; then place it under a microwave field, set the microwave power to 200W, use microwave heating to heat the preset current collector temperature to 150°C, then cool it down by 50°C, repeat the heating and cooling steps 3 times, and cool it down to room temperature after the last heating; then dry the remaining solvent to obtain a solid electrolyte with a preset current collector.

[0071] Comparative Example 1 of the present invention is:

[0072] The only difference between Comparative Example 1 and Example 1 is: S3, placing the substrate on a glass table, casting the electrolyte pre-coating liquid on the substrate using a casting method, drying at 50°C for 11 hours, and forming an electrolyte film with a thickness of 100 um on the substrate; then drying the remaining solvent to obtain a solid electrolyte with a pre-set current collector.

[0073] Comparative Example 2 of the present invention is: a method for preparing a solid electrolyte, the steps are as follows:

[0074] S1. Prepare electrolyte pre-coating solution: dissolve 1.8 g PEO, 0.2 g PAN and 0.15 g LTFSI in 30 mL mixed solvent and stir magnetically for 20 h to obtain electrolyte pre-coating solution; the mixed solvent is composed of DMF and acetonitrile in a mass ratio of 1:2.

[0075] S2. Pour the electrolyte pre-coating liquid into a mold and dry it at 50° C. for 11 hours to form an electrolyte membrane with a thickness of 100 μm; then dry the remaining solvent to obtain a solid electrolyte.

[0076] The following tests were performed on the solid electrolytes with pre-set current collectors prepared in Example 1, Comparative Example 1 and Comparative Example 2:

[0077] 1. Impedance test, test results see Figure 1 , Figure 1 The horizontal axis represents the real part of impedance, and the vertical axis represents the imaginary part of impedance.

[0078] 2. Ionic conductivity: The solid electrolytes with pre-set current collectors prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively assembled into button cells, and the ionic conductivity of the button cells was tested at 50° C., with a frequency range of 0.01 Hz to 1 MHz. The test results are shown in Table 1.

[0079] The assembly method of the button battery is as follows: the electrolyte film of the prefabricated current collector is cut into discs with a diameter of 18 mm, two stainless steel discs with a diameter of 16 mm and a thickness of 0.5 mm are used as double blocking electrodes, and a button battery of a stainless steel sheet-prefabricated current collector electrolyte film-stainless steel sheet structure is assembled.

[0080] 3. Cycle performance test: The solid electrolytes with pre-set current collectors prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively prepared into solid-state lithium-ion batteries, and the cycle performance of the solid-state lithium-ion batteries was tested. After the solid-state lithium-ion batteries were activated at 50°C and 0.1C for 3 times, they were charged and discharged at a rate of 1C, with a charge and discharge cut-off voltage of 4.8V-2.0V, and 1C cycled 200 times. The test results are shown in Figure 2 and Table 1, Figure 2 The horizontal axis represents the number of battery cycles, and the vertical axis represents the battery capacity. The higher the capacity retention rate, the tighter the bond between the current collector and the electrolyte, that is, the longer the life of the current collector.

[0081] The preparation method of the solid-state lithium-ion battery is as follows: a lithium-rich manganese-based material, conductive carbon, and PVDF binder are mixed in a mass ratio of 8:1:1, and an NMP dispersant is added to obtain a positive electrode slurry; the positive electrode slurry is coated on a 10um aluminum foil with a coating thickness of 60um, and then dried in a vacuum oven at 110°C to obtain an electrode sheet; the dried electrode sheet is rolled, and the compacted density of the active material is 2mg / cm 3 The positive electrode sheet is cut and then stacked with the solid electrolyte containing the pre-set current collector, heated to 60°C, and pressed under a pressure of 5Mp, and then assembled with the 2035 battery shell, gasket, and spring sheet into a solid-state lithium-ion battery.

[0082] Table 1

[0083] Example 1 Comparative Example 1 Comparative Example 2 Impedance(Ω) 390.7 410.3 715.6 50℃ ionic conductivity (S / cm) <![CDATA[4.3×10 -4 ]]> <![CDATA[3.1×10 -4 ]]> <![CDATA[6.2×10 -5 ]]> 200 cycles capacity retention rate (cycle life) 80.6% 70.3% 49.4%

[0084] Please refer to Figure 3 Embodiment 4 of the present invention is: an electrolyte for a negative electrode-free solid-state battery prepared by the preparation method of Embodiment 1, comprising a polymer electrolyte layer 1 and a foam copper current collector layer 2 arranged from top to bottom, wherein tin metal particles 3 are embedded in the foam copper current collector layer.

[0085] In summary, the negative electrode-free solid-state battery electrolyte and the preparation method thereof provided by the present invention have the following advantages:

[0086] 1. Immerse the foam copper sheet in an impregnation solution containing lithium-affinity metal and lithium-supplementing salt to obtain a pre-set current collector loaded with abundant lithium-affinity sites, which can extend the service life of the current collector.

[0087] 2. Under the action of microwaves, the foam copper current collector with micropores on the surface forms a close "gear-shaped" combination with the electrolyte layer, which promotes the ion and electron conductivity on the solid electrolyte / negative electrode current collector side and improves the compatibility of the contact interface between the current collector layer and the electrolyte layer.

[0088] 3. Li-Sn alloy is generated at the interface between the electrolyte and the current collector, which can guide the deposition of lithium on the current collector and improve the cycle stability of the battery. The source of Li-Sn alloy is two parts. The first part is SnCl built into the current collector before the battery cycle. 2 and LiClO 4 The second part is to induce shuttle lithium deposition to form Li-Sn alloy and stabilize the interface structure during the battery cycle.

[0089] 4. Pre-setting the negative electrode side current collector on the electrolyte can reduce the assembly steps and improve engineering efficiency.

[0090] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing an electrolyte for a negative electrode-free solid-state battery, characterized in that: The following steps are involved: The copper foam sheet is immersed in an impregnation solution containing a lithium-philic metal and a lithium-supplementing salt to obtain a substrate; an electrolyte pre-coating solution is poured on the substrate, and after drying and microwave curing, a solid electrolyte with a pre-set current collector is obtained; The microwave curing is specifically as follows: placing the dried material under a microwave field, setting the microwave power to 200-400W, heating the microwave temperature to 100-150°C, then cooling it down by 10-50°C, repeating the heating and cooling steps at least twice, and cooling it down to room temperature after the last heating.

2. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 1, characterized in that: The preparation method of the impregnation solution is specifically as follows: adding stannous chloride, lithium supplement salt, lithium-philic metal and dispersant into ethanol, and performing ultrasonic dispersion to form the impregnation solution.

3. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 2, characterized in that: The lithium-philic metal is tin powder.

4. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 2, characterized in that: The dispersant is OP-10 or NMP.

5. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 2, characterized in that: In parts by weight, the impregnation solution includes 2 to 5 parts of stannous chloride, 1.5 to 30 parts of lithium supplementing salt and 0.1 to 20 parts of lithium-philic metal.

6. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 1, characterized in that: The preparation method of the electrolyte pre-coating liquid is as follows: PEO, PAN and an organic lithium salt are dissolved in a mixed solvent of DMF and acetonitrile and stirred to obtain the electrolyte pre-coating liquid.

7. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 6, characterized in that: The mass ratio of the PEO, PAN and organic lithium salt is 10-19:1-10:1-5.

8. The method for preparing an electrolyte for a negative electrode-free solid-state battery according to claim 1, characterized in that: After drying, the film thickness formed by the electrolyte pre-coating liquid is 20 to 260 μm.

9. An electrolyte for a negative electrode-free solid-state battery prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite solid electrolyte and lithium ion battery comprising same

    CN113285117A

  • Electrolyte sheet with SSE surface modified by metal oxide and solid-state lithium battery without negative electrode

    CN115911524A

  • Negative-electrode-free lithium metal battery, negative electrode current collector of negative electrode-free lithium metal battery and preparation method

    CN113013417A

  • Lithium-free negative pole piece, preparation method thereof and lithium battery

    CN117438533A

  • Silver-carbon composite negative electrode and method for optimizing solid-state battery interface

    CN118572036A